2016
DOI: 10.1016/j.rbmo.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammatory and angiogenesis mediators in a functional model of decidualized endometrial stromal cells

Abstract: Québec-HSFA in Canada. His research team was internationally renowned for its major contributions to the understanding of the pathogenesis of endometriosis, as well as for its more recent studies on the molecular and cellular aspects of embryo implantation. He will be remembered fondly as a good friend, wonderful colleague, collaborator and mentor. AbstractThe mechanisms involving the expression of interleukin (IL) 1 family members in the process of preparing the endometrium to receive an embryo remain unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Similar findings were also reported by Piccirilli et al (2018). It was also reported that in the uterus, expression of TRa and TRb were mainly localized to the macrophages and dendritic cells (De Vito et al, 2011), where these cells are involved in the implantation-related inflammatory processes (Bourdiec et al, 2016). Apart from the increased in TR expression in the endometrium, expression of TRa and TRb was also reported to increase in the blastocyst at the time of implantation (Colicchia et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar findings were also reported by Piccirilli et al (2018). It was also reported that in the uterus, expression of TRa and TRb were mainly localized to the macrophages and dendritic cells (De Vito et al, 2011), where these cells are involved in the implantation-related inflammatory processes (Bourdiec et al, 2016). Apart from the increased in TR expression in the endometrium, expression of TRa and TRb was also reported to increase in the blastocyst at the time of implantation (Colicchia et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that only sex-steroids, in particular progesterone is required to induce expression of these proteins in the uterus. It was also reported that in the uterus, expression of TRa and TRb were mainly localized to the macrophages and dendritic cells (De Vito et al, 2011), where these cells are involved in the implantation-related inflammatory processes (Bourdiec et al, 2016). Besides regulating these uterine proteins' expression, thyroid hormone (TH) has also been reported been reported to be essential for blastocyst development (Norwitz et al, 2001;Dey et al, 2004;Cheong et al, 2013) as well as has been reported to be involved in stimulating endothelial proliferation (Staun-Ram and Shalev, 2005;Demir et al, 2010) uterine tissue remodeling and angiogenesis (Dey et al, 2004;Plaisier, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, mechanical injury of the endometrium may enhance uterine receptivity by provoking the immune system to generate an inflammatory reaction . Acquisition of uterine receptivity is closely associated with an inflammatory response . In this meta‐analysis, we find that even diagnostic hysteroscopy can lead to positive effects on IVF/ICSI outcomes, albeit the endometrial injury minor compared with pipelle biopsy.…”
Section: Discussionmentioning
confidence: 81%
“…The interleukin 36 gamma gene (IL36G) is part of the interleukin 1 (IL1) cytokine family. During decidualization of human endometrial stromal cells, cell receptivity to the IL1 family is modulated [50], suggesting a role in endometrial receptivity. Endometrial expression of these three genes is stimulated by the presence of a more advanced conceptus, presumably as a result of specific factors expressed by the conceptus that help modulate the uterine environment to better support the development of a more advanced conceptus.…”
Section: Discussionmentioning
confidence: 99%